2022
DOI: 10.1021/acs.est.2c03856
|View full text |Cite
|
Sign up to set email alerts
|

Co-Exposure of Ambient Particulate Matter and Airborne Transmission Pathogens: The Impairment of the Upper Respiratory Systems

Abstract: Recent evidence has pinpointed the positive relevance between air particulate matter (PM) pollution and epidemic spread. However, there are still significant knowledge gaps in understanding the transmission and infection of pathogens loaded on PMs, for example, the interactions between pathogens and pre-existing atmospheric PM and the health effects of co-exposure on the inhalation systems. Here, we unraveled the interactions between fine particulate matter (FPM) and Pseudomonas aeruginosa (P. aeruginosa) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Air pollution has become one of the key environmental crises, , associated with considerable detrimental human health outcomes. Among air pollutants, ambient fine particles (AFPs, commonly known as fine particulate matter or PM 2.5 ) are gaining increasing attention in public health. Strikingly, emerging studies suggested that the AFP pollution could not only affect the eye surface, such as eye discomfort, aberrant tear morphology, and ocular surface inflammation, but also have indirect adverse effects on the inner structures of eyes through inflammatory cytokines. Liu et al previously reported the presence of black carbon particles at the ocular surface and found a positive association with dry eye disease . AFPs are laden with various pollutants (e.g., heavy meal, polycyclic aromatic hydrocarbons, and pathogens) and will transform once in the biological microenvironment, generating reactive oxygen species (ROS) and bringing unpredicted health risks . It should be noted that the inner structure of the eye is delicate and fragile, built up by muscles, collagenous fiber, thousands of vessels, and millions of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution has become one of the key environmental crises, , associated with considerable detrimental human health outcomes. Among air pollutants, ambient fine particles (AFPs, commonly known as fine particulate matter or PM 2.5 ) are gaining increasing attention in public health. Strikingly, emerging studies suggested that the AFP pollution could not only affect the eye surface, such as eye discomfort, aberrant tear morphology, and ocular surface inflammation, but also have indirect adverse effects on the inner structures of eyes through inflammatory cytokines. Liu et al previously reported the presence of black carbon particles at the ocular surface and found a positive association with dry eye disease . AFPs are laden with various pollutants (e.g., heavy meal, polycyclic aromatic hydrocarbons, and pathogens) and will transform once in the biological microenvironment, generating reactive oxygen species (ROS) and bringing unpredicted health risks . It should be noted that the inner structure of the eye is delicate and fragile, built up by muscles, collagenous fiber, thousands of vessels, and millions of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The particulate matters with an aerodynamic diameter below 2.5 μm (PM 2.5 ) are characterized by large specific surface area, long propagation distance, and high susceptibility to carry various hazardous substances such as pathogens and heavy metal. Exposure to PM 2.5 has been evidenced to ingress the respiratory and circulatory systems, thereby instigating a spectrum of ailments, encompassing cardiovascular diseases and asthma. , The use of polymeric air filters provide an economical and effective way to capture PM 2.5 in a variety of scenarios, such as medical workplaces and public transportation. , The melt-blown microfibers have been widely used for traditional filtration layer of air filters, such as polypropylene (PP) and poly(vinylidene difluoride) (PVDF). However, the lifetime of these traditional air filters is relatively short because the electrostatic charge on the surface of fiber dissipates, when PMs and water vapor deposit on the filter during the process of utilization. The rapid dissipation of charge means inefficient protection and frequent replacement, which cause environmental burden. , Moreover, most air filters release microplastics, causing obstruction, inflammation and oxidative stress diseases. Therefore, it is of paramount significance to develop high-performance air filters of good degradability, superior filtration efficiency, reliable humidity resistance and long lifetime.…”
Section: Introductionmentioning
confidence: 99%